Anchorage Zone Stresses Model of Interior Diaphragm for Segmental Box Girder Bridge - Ghassan M. Werdina; Omar Q. Aziz (Polytechnic Journal)
Post-tensioning tendons in segmental box girder bridges are usually anchored in very massive diaphragms. This paper presents an analytical investigation of the anchorage zone stresses for an interior pier diaphragm and a rectangular block model (model of diaphragm anchorage zone). The failure load and load-displacement relation for the two cases were compared, a typical diaphragm for a segmental box girder bridge with external prestressing tendons and rectangular block model were analyzed by finite element program (ABAQUS). The anchorage devices were subjected to a prestressing design load which was based on the ultimate strength of the tendons. The magnitude and distribution of stresses were plotted through different paths for both the diaphragm and the block model; also the contours of stress distribution for the diaphragm and block model were compared. The results showed that the stresses and failure load for the diaphragm and rectangular block model were very close.